ANALISA CEMARAN LOGAM MERKURI PADA IKAN AIR TAWAR DAN UDANG AIR TAWAR SECARA SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Zuhairiah, Zuhairiah; Sitompul, Erly; Sitorus, Elly; Silalahi, Yosy Cinthya Eriwaty (Jurnal Farmanesia, 2019)
Fish containing mercury will have a bad impact on the health of the human body. The maximum limit of mercury levels in fish that has been determined by SNI (2009) on fish is 0.5 mg/kg. This study aims to determine the presence or absence of mercury (Hg) metal contamination in several types of freshwater fish, namely catfish (Clariasgariepinus), catfish (Pangsiushypophthalmus), tilapia (Oreochromis mossambicus), tilapia (Oreochromis niloticus), pomfret (Colossomamacropomum) and giant prawn (Macrobrachiumrosenbergii), by Atomic Absorption Spectrophotometry (AAS). Quantitative analysis of mercury used atomic absorption spectrophotometry (Shimadzu AA-6200). Measured at a wavelength of 253.7 nm. The results of this study were white pomfret containing mercury with levels of 0.2043 -+ 0.0079 mg/kg, catfish containing mercury with levels of 0.4116 -+ 0.1105 mg/kg, catfish containing mercury with levels of 0.4088 -+ 0.1076 mg/kg, tilapia fish contains mercury with levels of 0.4034 -+ 0.1443 mg/kg, tilapia fish contains mercury with levels of 0.4191 -+ 0.0750 mg/kg, and giant prawns contain mercury with levels of 0, 3928 -+ 0.0521 mg/kg. The calculation results show that all types of fresh water fish contain mercury <0.5 in accordance with the requirements set by SNI No.7387 (2009) on fish, namely 0.5 mg/kg.